الاستجواب في نطاق الدعوى المدنية : دراسة مقارنة - د. أوان عبدالله الفيضي (PROSPECTIVE RESEARCHES, 2023)
Interrogation is considered as one of the procedures of confirming evidence that is ordered by the Court itself. This can be in answer of one party request in a lawsuit concerned by asking the other party various questions… in order to get the truth, give other evidences towards making the right decisions toward the case, and enable the Court to reach the truth guided to this confirming. Thus, the importance of interrogation is represented as a method to gain the confession of the other party, which is here, as the master evidence. Although, it is rarely to be confessed by the other party himself, but mostly by asking and confronting him with the barefaced facts and that is done in presence of the other party to highlight, directly, the truth. The confession can be done by interrogating and asking him. So he can not deny the rights he is interrogated for. This, usually, settled in any session of the trail concerned. There for right and ambiguity are revealed to accomplish the justice.